2019
DOI: 10.1088/1555-6611/ab4dac
|View full text |Cite
|
Sign up to set email alerts
|

Temporal field and frequency spectrum of intense femtosecond radiation dynamics in the process of plasma formation in a dielectric medium

Abstract: We consider the propagation of intense femtosecond pulses in a dielectric medium with an induced plasma. This plasma is excited by the strong electric field of the pulses, stimulating sequential electron transition to the conductivity band through excited discrete energy states. It is demonstrated that this simple dynamic model of ultrashort optical pulse propagation in a dielectric medium with self-induced plasma can be applied to experiments on the superbroadening of the pulse spectrum into the long-waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…A theoretical model which describes the physics of ultrashort pulses has also been used in the THz generation from liquid water 147,148 . In this model, the dynamics of the radiation field, the evolution of the current density of quasi-free electrons, and the dynamics of the concentration of electrons have been included,…”
Section: Thz Generation From Liquid Plasma Induced By Singlecolor Pulsementioning
confidence: 99%
See 3 more Smart Citations
“…A theoretical model which describes the physics of ultrashort pulses has also been used in the THz generation from liquid water 147,148 . In this model, the dynamics of the radiation field, the evolution of the current density of quasi-free electrons, and the dynamics of the concentration of electrons have been included,…”
Section: Thz Generation From Liquid Plasma Induced By Singlecolor Pulsementioning
confidence: 99%
“…This dependence was also explored in the case of THz generation from liquid plasma. It was observed that from either water film or line, the optimal pulse duration for THz wave generation is in the order of subpicosecond 143,147,148,152 . This observation results from the dependence of plasma formation in water on the optical pulse duration, in which the electron density (corresponding to the pulse width) plays an important role 153 .…”
Section: Thz Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, multiphoton and tunneling ionization are more important in the case of gas. For more information on the theoretical analysis about single-color excitation, please check [15,50,62,63].…”
mentioning
confidence: 99%